Avo Inversion Using Levenberg-Marquardt Optimization Technique - Suprajitno Munadi; Humbang Purba (Scientific Contributions Oil and Gas, 2010)
AVO is not only well known as gas indicator over the last two decades but also more importantly, AVO provides us with a means for extracting petrophysical parameters from seismic data. Using AVO anomaly one can derive important petrophysical parameters such as Poisson’s ratio and S-wave velocity. By knowing S-wave velocity nearly all other petrophysical parameters can be calculated. An effective procedure for inverting AVO anomaly is presented in this paper. It avoids inefficient trial and error steps during the matching process between AVO anomaly and calculated AVO. This method uses Levenberg-Marquardt optimization technique.